2019
DOI: 10.5152/tjsm.2019.127
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Effects of Static and Dynamic Stretching Exercises on Dynamic Balance Performance

Abstract: Objective: The main purpose of this study was to investigate the acute effects of static and dynamic stretching exercises on dynamic balance. Materials and Methods: Sixty-seven recreational athletes (33 males aged 20.5 ± 2.3 yrs) and 34 females aged 21.4 ± 3.0 yrs) were tested in three different protocols including the control condition, static stretching, and dynamic stretching exercises on three separate days, 48-72 h apart. Before and after each protocol, double limb dynamic balance was tested on an isokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…The Y-balance test showed similar improvement in both intervention groups. Unilateral dynamic balance is especially critical for soccer players since most of their repetitive and explosive movements involve unilateral actions such as acceleration and deceleration tasks, rapid cutting maneuvers, kicking, jumping, and landing [ 49 , 50 ]. Therefore, poor unilateral dynamic balance can create unsafe situations for athletes and negatively impact their performance accuracy [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Y-balance test showed similar improvement in both intervention groups. Unilateral dynamic balance is especially critical for soccer players since most of their repetitive and explosive movements involve unilateral actions such as acceleration and deceleration tasks, rapid cutting maneuvers, kicking, jumping, and landing [ 49 , 50 ]. Therefore, poor unilateral dynamic balance can create unsafe situations for athletes and negatively impact their performance accuracy [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…A high degree of self-control makes the patient' s core strength, ankle joints, and body muscles participate in the training and strengthens cooperation. 10 The patient is training in an unstable space. This training method strengthens the functional dynamic stretching training and strengthens the coordination between the ankle joint and the small muscle groups of the whole body.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that practicing yoga during warm-up appeared to be more effective than dynamic stretching for improving balance performance. The effect of dynamic stretching on balance has been controversial [38, 39, 40, 41], while yoga has been shown to be positive for balance in different populations [42, 43, 44, 45]. The training of ankle flexibility and stability in yoga asana practice accounted for a large proportion [46, 47], which made it important for running, because ankle injuries accounted for 1/3 of running injuries [48] and ankle stability also affected the efficient in running [49].…”
Section: Discussionmentioning
confidence: 99%